Silicon carbide microreactor for ozone catalysis as well as preparation method and application of silicon carbide microreactor

By using metal oxide catalyst with sintered neck structure in the silicon carbide microreactor, the problems of low catalytic efficiency and poor stability of ozone are solved, and the effect of efficient degradation of dye wastewater is achieved.

CN119306314AActive Publication Date: 2025-01-14SHANGHAI UNIV OF ENG SCI +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411671213.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-01-14
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

In the prior art, the catalytic efficiency of ozone is low, it is difficult to deeply degrade dye wastewater, and the catalyst has poor stability and is prone to fall off, resulting in limited reaction kinetics and low ozone utilization.

Method used

Using a silicon carbide micro reactor, metal oxides are connected between silicon carbide particles in the form of sintered necks to form a three-dimensional network structure, which is used to catalyze ozone decomposition, improve the transfer rate and contact time of ozone in water, and enhance the organic matter. Degradation efficiency.

Benefits of technology

The treatment efficiency of dye wastewater is improved, secondary pollution is reduced, and the strong binding force of the catalyst and silicon carbide particles avoids falling off, forming an efficient ozone catalytic system, which significantly improves the dye degradation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306314A_ABST
    Figure CN119306314A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water treatment, in particular to a silicon carbide microreactor for ozone catalysis and a preparation method and application thereof. Comprising the following steps: S1, mixing silicon carbide powder, a metal oxide, a binder and a dispersant in a solvent, carrying out ball milling to obtain a slurry liquid, and drying to form a pug; s2, molding the obtained pug in a mold to obtain a green body; and S3, sintering the obtained blank in an inert gas atmosphere, and cooling to obtain the silicon carbide microreactor, thereby completing the reaction. Compared with the prior art, the method has the advantages that the metal oxide is connected among the silicon carbide particles in the form of the sintering neck, the formed sintering neck has an ozone catalysis function, a large number of microreactors with communicated three-dimensional networks are formed, and efficient degradation of the dye wastewater is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a silicon carbide microreactor for ozone catalysis and a preparation method and application thereof. Background Art

[0002] my country is a major textile production and consumption country. The annual use of dyes accounts for more than 83% of the world's total. The printing and dyeing industry generates a large amount of dye wastewater during the production process, which accounts for about 11% of the total industrial wastewater in the country. According to statistics, the annual output of textiles in my country can reach 80 million tons, and it is necessary to discharge up to 10 billion tons of dye wastewater. Dye wastewater has the characteristics of complex composition, high chroma, high chemical oxygen demand, difficult degradation, high toxicity, and difficulty in treatment. If dye wastewater is not treated up to standard, it will pollute nearby water bodies and soil, causing serious harm to the ecological environment. Therefore, researching and developing efficient, economical, and green dye wastewater treatment technology is an important measure for sustainable development.

[0003] As an advanced oxidation technology, ozone uses the strong oxidizing property of ozone (redox potential 2.07V) to oxidize and degrade organic pollutants in wastewater. It has the advantages of simple operation and low operating cost and is widely used in the field of industrial wastewater treatment. However, direct ozone oxidation has low catalytic efficiency and cannot deeply mineralize organic matter. Therefore, some metal oxides are used to catalyze ozone oxidation. Metal oxides can provide abundant active sites to accelerate the decomposition of ozone to produce active oxygen species and improve the degradation efficiency of organic matter. However, in the gas-liquid-solid three-phase ozone catalytic oxidation process, ozone is difficult to dissolve in water, and the bubble mass transfer resistance is large. It is difficult to reach the inside of the catalyst and act on the active sites, resulting in limited reaction kinetics and low ozone utilization. The patent (CN 104803512A) prepares a titanium-manganese or titanium-cerium catalyst layer on the surface of the ceramic membrane by dip coating, catalyzes ozone dissolved in water, and achieves a self-cleaning effect of the membrane. However, the catalyst layer has the risk of clogging the membrane pores, and the catalyst layer is easy to fall off during the backwashing process, resulting in poor stability. Summary of the invention

[0004] The purpose of the present invention is to provide a silicon carbide microreactor for ozone catalysis and its preparation method and application in order to overcome the defects of the above-mentioned prior art such as low ozone utilization rate. In the present invention, the metal oxide is connected between silicon carbide particles in the form of sintered necks, and the formed sintered necks have ozone catalytic function, forming a large number of microreactors with three-dimensional networks connected, so as to achieve efficient degradation of dye wastewater.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a method for preparing a silicon carbide microreactor for ozone catalysis, comprising the following steps:

[0007] S1, silicon carbide powder, metal oxide, binder and dispersant are mixed in a solvent, ball-milled to obtain a slurry, and dried to form a mud material;

[0008] S2, forming the obtained clay material in a mold to obtain a green body;

[0009] S3, sintering the obtained green body in an inert gas atmosphere, and obtaining a silicon carbide microreactor after cooling, and the reaction is completed.

[0010] Furthermore, in step S1, the metal oxide includes one or more of zinc oxide, cobalt oxide, iron oxide, manganese oxide, nickel oxide, and cerium oxide, which is different from the oxides such as aluminum oxide, magnesium oxide, zirconium oxide, and silicon dioxide commonly used in the prior art. The metal oxide of the present invention can form a sintering neck with ozone catalytic function.

[0011] The binder includes one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methylcellulose, carboxymethyl cellulose, carboxyethyl cellulose, and polyacrylic acid;

[0012] The dispersant includes one or more of tetramethylammonium hydroxide, sodium polyacrylate, ammonium polyacrylate, polycarbonate, polyethyleneimine, sodium alginate, and ammonium polymethacrylate;

[0013] The solvent includes ethanol and water.

[0014] Furthermore, in step S1, the mass volume ratio of the silicon carbide powder, metal oxide, binder, dispersant and solvent is (10-15): (2-10): (1-5): (0-2): (20-30).

[0015] Further, in step S1, the average particle size of the silicon carbide powder is 10 to 20 μm;

[0016] The average particle size of the metal oxide is 0.1 to 2 μm.

[0017] Furthermore, in step S2, the specific process of the molding is: dry-pressing the obtained clay material under a pressure of 20 to 40 MPa, drying it at room temperature for 6 to 24 hours, and then performing secondary dry-pressing molding under a pressure of 40 to 70 MPa to obtain a green body.

[0018] Furthermore, in step S3, the specific process of sintering is: heating the temperature to 800-900°C at a rate of 2-5°C / min and keeping it for 1-3h, then heating the temperature to 1200-1500°C at a rate of 2-5°C / min and keeping it for 1-3h.

[0019] The second technical solution of the present invention is to provide a silicon carbide microreactor for ozone catalysis, which is prepared by the preparation method, wherein the metal oxide with catalytic function in the silicon carbide microreactor acts as a sintering neck to adhere the silicon carbide particles to each other, forming a structure with a three-dimensional network penetration. The sintering neck is formed by melting the metal oxide at a high temperature.

[0020] Furthermore, the silicon carbide microreactor has a minimum pore size of 1 to 5 μm and a porosity of 60% to 80%.

[0021] The third technical solution of the present invention is to provide an application of a silicon carbide microreactor for ozone catalysis in the field of water treatment, wherein the silicon carbide microreactor is used to treat wastewater including Congo red, chrome black T, reactive red 195, reactive brilliant blue Kn-R, indigo, acid blue, and acid orange 52II.

[0022] A fourth technical solution of the present invention is to provide a water treatment system for ozone catalysis, wherein the silicon carbide microreactor is loaded into an upflow reaction tower.

[0023] Furthermore, the water treatment system further comprises:

[0024] A wastewater storage tank connected to the upflow reaction tower and used to store wastewater to be treated;

[0025] and an ozone generator connected to the upflow reaction tower, used for passing the generated ozone into the upflow reaction tower for catalysis, wherein the ozone generator is connected to the bottom of the upflow reaction tower.

[0026] Furthermore, a ball valve, a flow meter and an ozone detector are also connected to the pipeline connecting the ozone generator and the upflow reaction tower.

[0027] Furthermore, the water treatment system also includes a vacuum pump for circulating the treated effluent water back into the wastewater storage tank, and the vacuum pump is connected to the top of the upflow reaction tower.

[0028] The catalyst in the microreactor of the present invention can increase the ozone transfer rate and contact time in the water body, so that ozone decomposes to produce active oxygen species (such as hydroxyl free radicals OH, superoxide free radicals O2 ·- ), active oxygen can react with organic pollutants to degrade them. Compared with direct ozonation, the microreactor of the present invention has advantages in improving treatment efficiency and reducing secondary pollution. Among them, the catalyst selection and the sintering program control in step S3 have a significant impact on the formation of sintering necks.

[0029] Compared with the prior art, the present invention has the following advantages:

[0030] (1) The catalyst of the conventional supported catalytic ceramic membrane is distributed on the membrane surface and is easily lost during the reaction, causing secondary pollution. The catalyst of the present invention is distributed between the silicon carbide particles in the form of sintered necks, which greatly alleviates the problem of catalyst loss.

[0031] (2) When wastewater containing dissolved ozone passes through the silicon carbide support, the sintered neck structure formed by the metal oxide can effectively catalyze ozone to form hydroxyl radicals in a confined space, thereby improving the performance of ozone catalytic degradation of organic matter.

[0032] (3) The metal oxides and silicon carbide powders interpenetrate each other, effectively inhibiting the agglomeration of silicon carbide. Using metal oxides as sintering aids can form a low-viscosity liquid phase, promote atomic transfer at low temperatures, form sintering necks between silicon carbide particles, and effectively reduce the sintering temperature of silicon carbide.

[0033] (4) The traditional supported catalytic ceramic membrane is to coat or filter the catalyst on the surface of the silicon carbide membrane, which will block some membrane pores and is not conducive to ozone transmission. At the same time, the bonding force between the catalyst and silicon carbide is weak and easy to fall off. The present invention sinters the silicon carbide and the catalyst together to form a pore structure at the gap between the particles, and there is no problem of membrane pore clogging. In addition, the contact and bonding between the catalyst and silicon carbide reduces the surface energy, and the strong bonding force between the particles prevents the catalyst from falling off. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The metal oxide sintering neck structure of the silicon carbide microreactor in Example 1, A) SEM picture, B) structural schematic diagram;

[0035] Figure 2 The SEM images of the silicon carbide microreactor shown in each embodiment, A) embodiment 1, B) embodiment 2, C) embodiment 3;

[0036] Figure 3 1 is the contact angle of the silicon carbide microreactor shown in each embodiment, A) embodiment 1, B) embodiment 2, C) embodiment 3;

[0037] Figure 4 It is a schematic diagram of the water treatment system;

[0038] Figure 5 The degradation effect of the silicon carbide microreactor on the dye shown in each embodiment, A) embodiment 1, B) embodiment 2, C) embodiment 3, D) embodiment 6, E) embodiment 7, F) embodiment 8, G) embodiment 9, H) embodiment 10;

[0039] Figure 6 This is a morphology diagram of the pure silicon carbide support sintered at low temperature as shown in Comparative Example 1;

[0040] Figure 7This is the SEM image of the pure silicon carbide microreactor shown in Comparative Example 2;

[0041] Figure 8 The degradation effect of ozone on dyes catalyzed by the pure silicon carbide microreactor shown in Comparative Example 2;

[0042] Fig. 9 This is the degradation effect of single ozone on dye shown in Comparative Example 3.

[0043] Description of the markings in the figure:

[0044] 1- ozone generator, 2- ball valve, 3- flow meter, 4- ozone detector, 5- wastewater storage tank, 6- upflow reaction tower, 7- silicon carbide microreactor, 8- vacuum pump. DETAILED DESCRIPTION

[0045] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiments. Based on the given embodiments, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0046] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art.

[0047] In the following examples, the cobalt oxide nanoparticles (CAS No.: 1308-06-1) were purchased from Alfa Aesar (China) Chemical Co., Ltd.; polyvinyl alcohol (CAS No.: 9002-89-5) was purchased from Shanghai Huake Industrial Co., Ltd.; tetramethylammonium hydroxide (CAS No.: 75-59-2) was purchased from Alfa Aesar (China) Chemical Co., Ltd.; ethanol (CAS No.: 64-17-5) was purchased from Alfa Aesar (China) Chemical Co., Ltd.; silicon carbide powder (CAS No.: 409-21-2) was purchased from Zhejiang Carbon State Technology Co., Ltd.; dye steel Fruit red (CAS No.: 573-58-0) was purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Chrome black T (CAS No.: 1787-61-7) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd., Reactive Red 195 (CAS No.: 93050-79-4) was purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; Reactive brilliant blue Kn-R (CAS No.: 2580-78-1); indigo (CAS No.: 482-89-3); acid blue (CAS No.: 27360-85-6) were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0048] Example 1

[0049] A method for preparing a silicon carbide microreactor for ozone catalysis comprises weighing 35g of silicon carbide powder, 5g of cobalt oxide nanoparticles, 8g of 8wt% polyvinyl alcohol aqueous solution, 2g of 5wt% tetramethylammonium hydroxide aqueous solution, 50g of ethanol as ball milling dispersion, and 50g of ball milling balls in a ball milling jar, placing the ball milling jar in a planetary ball mill for 5h, dry pressing the obtained mud material under a pressure of 30MPa, drying it at room temperature for 12h, and then performing secondary dry pressing under a pressure of 50MPa to obtain a green body. After the green body is dried, it is placed in a graphite furnace for pressureless sintering in an argon atmosphere, and the sintering procedure is: first, heating to 850°C at a heating rate of 3°C / min and keeping the temperature for 2h, then heating to 1400°C at a rate of 3°C / min and keeping the temperature for 2h; after the heat preservation is completed, it is naturally cooled to room temperature with the furnace to obtain a silicon carbide microreactor 7.

[0050] Characterization and dye degradation performance evaluation of the prepared microreactor 7 at room temperature

[0051] Characterization method 1: Scanning electron microscopy was used to characterize the surface morphology of the microreactor.

[0052] The results show that the microreactor has a large amount of cobalt oxide in the form of sintering necks ( Figure 1 and Figure 2 A).

[0053] Characterization method 2: Use a contact angle meter to test the contact angle of the microreactor.

[0054] The results show that the contact angle of the microreactor is 10°( Figure 3 A), showing hydrophilic properties.

[0055] Characterization method 3: The pore size of the microreactor was measured using a mercury intrusion instrument, and the compressive strength of the microreactor was tested using a strength tester.

[0056] The results show that the microreactor has a maximum pore size of 4.36 μm and a compressive strength of 45.73 MPa (Table 1).

[0057] Test method 1: Evaluation of the microreactor's performance on dye degradation.

[0058] A water treatment system for ozone catalysis, wherein the silicon carbide microreactor 7 is loaded into an upflow reaction tower 6. The water treatment system comprises:

[0059] A wastewater storage tank 5 connected to the upflow reaction tower 6 and used to store wastewater to be treated;

[0060] The ozone generator 1 connected to the upflow reaction tower 6 is used to pass the generated ozone into the upflow reaction tower 6 for catalysis. The ozone generator 1 is connected to the bottom of the upflow reaction tower 6.

[0061] In this embodiment, a ball valve 2, a flow meter 3, and an ozone detector 4 are also connected to the pipeline connecting the ozone generator 1 and the upflow reaction tower 6.

[0062] In this embodiment, the water treatment system further comprises a vacuum pump 8 for circulating the treated effluent water back into the wastewater storage tank, and the vacuum pump 8 is connected to the top of the upflow reaction tower 6 .

[0063] like Figure 4 As shown, the silicon carbide microreactor 7 prepared above is placed in an upflow reaction tower 6, and a Congo red solution with a concentration of 100 mg / L is prepared in a wastewater storage tank 5. The ozone generator 1, ball valve 2, flowmeter 3 and ozone detector 4 are connected, and the outlet of the ozone detector 4 is connected to the lower part of the upflow reaction tower 6. After in-situ aeration and mixing with the dye wastewater, the upper end of the upflow reaction tower 6 circulates the ozone-catalyzed effluent into the wastewater storage tank 5 through a vacuum pump 8. Samples are taken at certain time intervals to test the absorbance of the Congo red dye at the maximum absorption wavelength, and the dye degradation rate is calculated. The results show that the silicon carbide microreactor 7 can efficiently catalyze the degradation of the organic dye Congo red by ozone, and the dye can be degraded by nearly 100% within 120 minutes ( Figure 5 A).

[0064] Example 2

[0065] A method for preparing a silicon carbide microreactor for ozone catalysis, compared with Example 1, the other conditions remain unchanged, and only the cobalt oxide content is changed. That is:

[0066] 30g of silicon carbide powder, 10g of cobalt oxide nanoparticles, 8g of 8wt% polyvinyl alcohol aqueous solution, 2g of 5wt% tetramethylammonium hydroxide aqueous solution, 50g of ethanol as ball milling dispersion, and 50g of ball milling balls were weighed into a ball milling jar, and placed in a planetary ball mill for 5h to obtain green clay. After the green body was dried, it was placed in a graphite furnace for pressureless sintering under an argon atmosphere. The sintering procedure was as follows: first, the temperature was raised to 850℃ at a rate of 3℃ / min and kept for 2h, then the temperature was raised to 1400℃ at a rate of 3℃ / min and kept for 2h; after the heat preservation was completed, it was naturally cooled to room temperature with the furnace to obtain silicon carbide microreactor 7.

[0067] The prepared microreactor was characterized and the dye degradation performance was evaluated at room temperature.

[0068] Characterization method 1: Scanning electron microscopy was used to characterize the surface morphology of the microreactor.

[0069] The results show that the microreactor has a large amount of cobalt oxide in the form of sintering necks ( Figure 2 B).

[0070] Characterization method 2: Use a contact angle meter to test the contact angle of the microreactor.

[0071] The results show that the contact angle of the microreactor can reach 5°( Figure 3 B), showing superhydrophilic properties.

[0072] Characterization method 3: The pore size of the microreactor was measured using a mercury intrusion instrument, and the compressive strength of the microreactor was tested using a strength tester.

[0073] The results show that the microreactor has a maximum pore size of 3.65 μm and a compressive strength of 43.57 MPa (Table 1).

[0074] Test method 1: Evaluate the dye degradation performance of the silicon carbide microreactor 7 of Example 2. The test was conducted using a water treatment system, which was mostly the same as the water treatment system in Example 1, except that the silicon carbide microreactor 7 was replaced by the silicon carbide microreactor 7 in Example 2. The results showed that the silicon carbide microreactor 7 could efficiently catalyze the ozone degradation of the organic dye Congo red, and the dye could be degraded by nearly 100% within 80 minutes ( Figure 5 B).

[0075] Example 3

[0076] A method for preparing a silicon carbide microreactor for ozone catalysis, compared with Example 1, the other conditions remain unchanged, and only the cobalt oxide content is changed. That is:

[0077] 25g of silicon carbide powder, 15g of cobalt oxide nanoparticles, 8g of 8wt% polyvinyl alcohol aqueous solution, 2g of 5wt% tetramethylammonium hydroxide aqueous solution, 50g of ethanol as ball milling dispersion, and 50g of ball milling balls were weighed into a ball milling jar, and placed in a planetary ball mill for 5h to obtain a green body mud. After the green body was dried, it was placed in a graphite furnace for pressureless sintering under an argon atmosphere. The sintering procedure was: first, the temperature was increased to 850℃ at a rate of 3℃ / min and kept for 2h, then increased to 1400℃ at a rate of 3℃ / min and kept for 2h; after the heat preservation was completed, it was naturally cooled to room temperature with the furnace to obtain a silicon carbide microreactor 7.

[0078] The prepared microreactor was characterized and the dye degradation performance was evaluated at room temperature.

[0079] Characterization method 1: Scanning electron microscopy was used to characterize the surface morphology of the microreactor.

[0080] The results show that the microreactor has a large amount of cobalt oxide in the form of sintering necks ( Figure 2 C).

[0081] Characterization method 2: Use a contact angle meter to test the contact angle of the microreactor.

[0082] The results show that the contact angle of the microreactor reaches 0° ( Figure 3 C), showing superhydrophilic properties.

[0083] Characterization method 3: The pore size of the microreactor was measured using a mercury intrusion instrument, and the compressive strength of the microreactor was tested using a strength tester.

[0084] The results show that the microreactor has a maximum pore size of 3.24 μm and a compressive strength of 42.68 MPa (Table 1).

[0085] Test method 1: Evaluate the dye degradation performance of the silicon carbide ozone microreactor 7 of Example 3. The test was conducted using a water treatment system, which was mostly the same as the water treatment system in Example 1, except that the silicon carbide microreactor 7 was replaced by the silicon carbide microreactor 7 in Example 3. The results showed that the silicon carbide microreactor 7 could efficiently catalyze the ozone degradation of the organic dye Congo red, and the dye could be degraded by nearly 100% within 60 minutes ( Figure 5 C). However, compared with Example 2, the degradation effects of the two are very different, but the concentration of cobalt oxide used in Example 3 is higher, indicating that the concentration of cobalt oxide in Example 2 can be regarded as the best.

[0086] Example 4

[0087] A method for preparing a silicon carbide microreactor for ozone catalysis, compared with Example 1, the other conditions remain unchanged, and only the green body sintering procedure is changed. That is:

[0088] After the green body is dried, it is placed in a graphite furnace for pressureless sintering in an argon atmosphere. The sintering procedure is as follows: first, the temperature is raised to 800°C at a rate of 2°C / min and kept for 2 hours, then the temperature is raised to 1200°C at a rate of 2°C / min and kept for 2 hours; after the insulation is completed, it is naturally cooled to room temperature in the furnace to obtain a silicon carbide microreactor 7.

[0089] At room temperature, the pore size of the microreactor was measured using a mercury intrusion instrument, and the compressive strength of the microreactor was tested using a strength tester.

[0090] The results show that the microreactor has a maximum pore size of 3.85 μm and a compressive strength of 44.38 MPa (Table 1).

[0091] Example 5

[0092] A method for preparing a silicon carbide microreactor for ozone catalysis, compared with Example 1, other conditions remain unchanged, only the green body sintering procedure is changed, and finally a silicon carbide microreactor 7 is obtained. That is:

[0093] After the green body is dried, it is placed in a graphite furnace for pressureless sintering in an argon atmosphere. The sintering procedure is as follows: first, the temperature is raised to 900°C at a rate of 5°C / min and kept for 2 hours, then the temperature is raised to 1500°C at a rate of 5°C / min and kept for 2 hours; after the insulation is completed, it is naturally cooled to room temperature in the furnace to obtain a silicon carbide catalytic microreactor 7.

[0094] At room temperature, the pore size of the microreactor was measured using a mercury intrusion instrument, and the compressive strength of the microreactor was tested using a strength tester.

[0095] The results show that the microreactor has a maximum pore size of 3.36 μm and a compressive strength of 45.63 MPa (Table 1).

[0096] Example 6

[0097] An application of a silicon carbide microreactor for ozone catalysis to degrade dyes, compared to Example 1, the other conditions remain unchanged, only the type of dye is changed, that is:

[0098] A 100 mg / L chrome black T solution was prepared and degraded using the water treatment system equipped with the silicon carbide microreactor 7 of Example 1. Samples were taken at certain time intervals to test the absorbance of the chrome black T dye at the maximum absorption wavelength and calculate the degradation rate of the dye. The results showed that the silicon carbide microreactor can efficiently catalyze the ozone degradation of the organic dye chrome black T, and the chrome black T dye can be degraded by nearly 100% within 40 minutes ( Figure 5 D).

[0099] Example 7

[0100] An application of a silicon carbide microreactor for ozone catalysis to degrade dyes, compared to Example 1, the other conditions remain unchanged, only the type of dye is changed, that is:

[0101] A solution of Reactive Red 195 with a concentration of 100 mg / L was prepared and degraded using the water treatment system of Example 1 equipped with the silicon carbide microreactor 7. The silicon carbide microreactor took samples at certain time intervals, tested the absorbance of the Reactive Red 195 dye at the maximum absorption wavelength, and calculated the degradation rate of the dye. The results showed that the silicon carbide microreactor 7 can efficiently catalyze the degradation of the organic dye Reactive Red 195 by ozone, and the dye can be degraded by nearly 100% within 80 minutes ( Figure 5 E).

[0102] Example 8

[0103] An application of a silicon carbide microreactor for ozone catalysis to degrade dyes, compared to Example 1, the other conditions remain unchanged, only the type of dye is changed, that is:

[0104] A 100 mg / L acid orange 52II solution was prepared and degraded using the water treatment system of Example 1 equipped with the silicon carbide microreactor 7. The silicon carbide microreactor 7 took samples at certain time intervals, tested the absorbance of the acid orange 52II dye at the maximum absorption wavelength, and calculated the degradation rate of the dye. The results showed that the silicon carbide microreactor 7 can efficiently catalyze the ozone degradation of the organic dye acid orange 52II, and the dye can be degraded by nearly 100% within 60 minutes ( Figure 5 F).

[0105] Example 9

[0106] An application of a silicon carbide microreactor for ozone catalysis to degrade dyes, compared to Example 1, the other conditions remain unchanged, only the type of dye is changed, that is:

[0107] A 100 mg / L active brilliant blue Kn-R solution was prepared and degraded using the water treatment system of Example 1 equipped with the silicon carbide microreactor 7. The silicon carbide microreactor 7 took samples at certain time intervals, tested the absorbance of the active brilliant blue Kn-R dye at the maximum absorption wavelength, and calculated the degradation rate of the dye. The results showed that the silicon carbide microreactor 7 can efficiently catalyze the ozone degradation of the organic dye active brilliant blue Kn-R, and the dye can be degraded by nearly 100% within 60 minutes ( Figure 5 G).

[0108] Example 10

[0109] An application of a silicon carbide microreactor for ozone catalysis to degrade dyes, compared to Example 1, the other conditions remain unchanged, only the type of dye is changed, that is:

[0110] An indigo solution with a concentration of 100 mg / L was prepared and degraded using the water treatment system equipped with the silicon carbide microreactor 7 of Example 1. The silicon carbide microreactor took samples at certain time intervals, tested the absorbance of the indigo dye at the maximum absorption wavelength, and calculated the dye degradation rate. The results showed that the silicon carbide microreactor 7 can efficiently catalyze the ozone degradation of the organic dye indigo, and the dye can be degraded by nearly 100% within 60 minutes ( Figure 5 H).

[0111] Embodiment 11

[0112] An application of a silicon carbide microreactor for ozone catalysis to degrade dyes, compared to Example 1, the other conditions remain unchanged, only the type of dye is changed, that is:

[0113] A 100 mg / L acid blue solution was prepared and degraded using the water treatment system loaded with the silicon carbide microreactor 7 of Example 1. The silicon carbide microreactor took samples at a certain time interval, tested the absorbance of the acid blue dye at the maximum absorption wavelength, and calculated the dye degradation rate. The results showed that the silicon carbide microreactor 7 can efficiently catalyze the ozone degradation of the organic dye acid blue, and the dye can be degraded by nearly 100% within 60 minutes.

[0114] Comparative Example 1

[0115] Compared with Example 1, the other conditions remain unchanged, but no metal oxide is added and the green body is sintered at a lower temperature.

[0116] Weigh 40g of silicon carbide powder, 8g of 8wt% polyvinyl alcohol aqueous solution, 2g of 5wt% tetramethylammonium hydroxide aqueous solution, 50g of ethanol as ball milling dispersion, and 50g of ball milling balls in a ball milling jar, place in a planetary ball mill for 5h, dry press the obtained mud under 30MPa pressure, dry at room temperature for 12h, and then dry press again under 50MPa pressure to obtain a green body. After the green body is dried, it is placed in a graphite furnace for pressureless sintering in an argon atmosphere. The sintering procedure is: first increase the temperature to 850℃ at a rate of 3℃ / min and keep it for 2h, then increase the temperature to 1400℃ at a rate of 3℃ / min and keep it for 2h; after the insulation is completed, naturally cool to room temperature with the furnace to obtain a pure silicon carbide support.

[0117] The surface morphology of the prepared microreactor was photographed at room temperature.

[0118] The results show that at low temperatures, pure silicon carbide supports lacking cobalt oxide nanoparticles cannot be sintered effectively, and the powder can be wiped off with a slight touch of the hand ( Figure 6 ).

[0119] Comparative Example 2

[0120] Compared with Example 1, the other conditions remain unchanged, but no metal oxide is added to prevent the catalyst sintering neck structure from appearing.

[0121] Weigh 40g of silicon carbide powder, 8g of 8wt% polyvinyl alcohol aqueous solution, 2g of 5wt% tetramethylammonium hydroxide aqueous solution, 50g of ethanol as ball milling dispersion, and 50g of ball milling balls in a ball milling jar, and place them in a planetary ball mill for 5h to obtain a mud material. The obtained mud material is dry pressed at a pressure of 30MPa, dried at room temperature for 12h, and then dry pressed again at a pressure of 50MPa to obtain a green body. After the green body is dried, it is placed in a graphite furnace for pressureless sintering in an argon atmosphere. The sintering procedure is: first, the temperature is increased to 850℃ at a rate of 3℃ / min and kept for 2h, then increased to 1900℃ at a rate of 3℃ / min and kept for 2h; after the insulation is completed, it is naturally cooled to room temperature with the furnace to obtain a microreactor.

[0122] The morphology of the microreactor was characterized by scanning electron microscopy at room temperature.

[0123] The results show that the film morphology is complete after high temperature sintering, but there is no metal cobalt oxide sintering neck between the pure silicon carbide particles without adding cobalt oxide nanoparticles. However, compared with Examples 1-3, high temperature sintering makes the silicon carbide particles morphology tend to be rounded ( Figure 7 )

[0124] Test method 1: Evaluate the dye degradation performance of the microreactor of comparative example 2. The results show that the degradation rate of the dye by the pure silicon carbide microreactor within 120 minutes is 80%, but compared with Example 2, the degradation effect of comparative example 2 on Congo red dye is limited, indicating that pure silicon carbide cannot effectively catalyze ozone to produce active oxygen species ( Figure 8 ).

[0125] Comparative Example 3

[0126] Compared with Example 1, the other conditions remain unchanged, and the silicon carbide microreactor 7 in Example 1 is not used for catalysis, that is:

[0127] The water treatment system was used for testing, most of which were the same as the water treatment system in Example 1, except that the silicon carbide microreactor 7 was not loaded. Ozone was directly mixed with the dye, and samples were taken at certain time intervals to test the absorbance of Congo red dye at the maximum absorption wavelength, calculate the dye degradation rate, and investigate the degradation effect of direct ozone oxidation on the dye. The results showed that the degradation rate of Congo red dye by the water treatment system was 80% within 120 minutes, which was basically the same as the degradation effect of Comparative Example 2, further indicating that pure silicon carbide in Comparative Example 2 could not effectively catalyze ozone to produce active oxygen species ( Fig. 9 ).

[0128] Table 1 shows the test performance of pore size, porosity and compressive strength of the silicon carbide microreactor of each embodiment.

[0129] Table 1 Performance of silicon carbide microreactor

[0130]

[0131] Although the present invention has been described in detail above by means of general description, specific implementation methods and tests, it is obvious to those skilled in the art that some modifications or improvements may be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a silicon carbide microreactor for ozone catalysis, characterized in that: The following steps are involved: S1, silicon carbide powder, metal oxide, binder and dispersant are mixed in a solvent, ball-milled to obtain a slurry, and dried to form a mud material; S2, forming the obtained clay material in a mold to obtain a green body; S3, sintering the obtained green body in an inert gas atmosphere, and obtaining a silicon carbide microreactor after cooling, and the reaction is completed.

2. The method for preparing a silicon carbide microreactor for ozone catalysis according to claim 1, characterized in that: In step S1, the metal oxide includes one or more of zinc oxide, cobalt oxide, iron oxide, manganese oxide, nickel oxide, and cerium oxide; The binder includes one or more of polyethylene glycol, polyvinyl alcohol, hydroxypropyl methylcellulose, carboxymethyl cellulose, carboxyethyl cellulose, and polyacrylic acid; The dispersant includes one or more of tetramethylammonium hydroxide, sodium polyacrylate, ammonium polyacrylate, polycarbonate, polyethyleneimine, sodium alginate, and ammonium polymethacrylate; The solvent includes ethanol and water.

3. The method for preparing a silicon carbide microreactor for ozone catalysis according to claim 1, characterized in that: In step S1, the mass ratio of the silicon carbide powder, metal oxide, binder, dispersant and solvent is (10-15): (2-10): (1-5): (0-2): (20-30).

4. The method for preparing a silicon carbide microreactor for ozone catalysis according to claim 1, characterized in that: In step S1, the average particle size of the silicon carbide powder is 10 to 20 μm; The average particle size of the metal oxide is 0.1 to 2 μm.

5. The method for preparing a silicon carbide microreactor for ozone catalysis according to claim 1, characterized in that: In step S2, the specific process of the molding is: dry-pressing the obtained clay material under a pressure of 20 to 40 MPa, drying it at room temperature for 6 to 24 hours, and then performing secondary dry-pressing molding under a pressure of 40 to 70 MPa to obtain a green body.

6. The method for preparing a silicon carbide microreactor for ozone catalysis according to claim 1, characterized in that: In step S3, the specific process of sintering is: heating the temperature to 800-900°C at a rate of 2-5°C / min and keeping it for 1-3h, then heating the temperature to 1200-1500°C at a rate of 2-5°C / min and keeping it for 1-3h.

7. A silicon carbide microreactor for ozone catalysis, which is prepared by the preparation method according to any one of claims 1 to 6, wherein the metal oxide with catalytic function in the silicon carbide microreactor acts as a sintering neck to bond the silicon carbide particles to each other, forming a structure with a three-dimensional network penetration.

8. The method for preparing a silicon carbide microreactor for ozone catalysis according to claim 7, characterized in that: The silicon carbide microreactor has a minimum pore size of 1 to 5 μm and a porosity of 60% to 80%.

9. The use of a silicon carbide microreactor for ozone catalysis in the field of water treatment as claimed in claim 7, characterized in that: The silicon carbide microreactor is used to treat wastewater including Congo red, chrome black T, reactive red 195, reactive brilliant blue Kn-R, indigo, acid blue and acid orange II.

10. A water treatment system for ozone catalysis, characterized in that: The silicon carbide microreactor according to claim 7 is loaded into an upflow reaction tower.

Citation Information

Patent Citations

  • Ozone catalytic oxidation and self-cleaning ceramic membrane combined water treatment method and device

    CN104803512A

  • Mesocarbon microbead reinforced silicon carbide based ceramic circuit board substrate material and preparation method thereof

    CN105837218A

  • Microporous overcurrent ozone catalytic ceramic membrane for waste water deep treatment as well as preparation method and application method thereof

    CN106745673A

  • Tablet catalytic ceramic membrane as well as forming method and forming equipment thereof

    CN107324780A

  • Aperture-controllable micron-aperture silicon carbide porous ceramic and preparation method thereof

    CN115340385A